Persepsi dan Sikap Dokter dalam Pemberian Surat Keterangan Cuti Sakit di RS PKU Muhammadiyah Yogyakarta - Soularto, Dirwan Suryo; Azhimsari, Ayu (Universitas Muhammadiyah Yogyakarta, 2008)
Doctor statement letter is a letter which is given by doctor professionally about a certain situation which is known and can be proven itâs truth. The aim of this research is to know the factors which influent the perception and behavior of doctor to give the sickness permission letter. The design of the research is non experimental. The subject of research is some doctors who work in PKUM uhammadiyah Hospital of Yogyakarta are 35 people. Responden who fulfill questioner about perception and attitude of doctor to give sickness permission letter. The analysis descriptive which is used with cross-sectional approach. The result of research is 63% agree every patient get a sickness permission letter, 60% disagree about the relation of friendship which influent the doctor to give sickness permission letter, 94% agree about the giving of period of sickness is a right of doctor absolutely, 71% disagree if doctor always give sickness permission letter to every patient who asked it, 74% doctor never give sickness permission letter which isn ât suitable with the patient âs condition, 60% doctor agree to give period of retirement sickness sometimes thinks the patientâs requirement, 97% doctor disagree to ask a certain free to give sickness permission letter. The conclusion of this research is perception and attitude of doctor in Muhammadiyah Hospital of Yogyakarta still suitable with etic of Indonesion medical.Surat keterangan dokter adalah surat yang diberikan oleh seorang dokter secara profesional mengenai keadaan tertentu yang diketahuinya dan dapat dibuktikan kebenarannya. Penelitian ini bertujuan untuk mengetahui faktor-faktor yangmempengaruhi persepsi dan sikap dokter dalam pemberian surat keterangan cuti sakit. Desain penelitian ini adalah non-eksperimental dengan pendekatan cross-sectional. Subyek penelitian adalah 35 orang dokter yang bekerja di RS PKU Muhammadiyah Yogyakarta. Responden mengisi kuesioner mengenai persepsi dan sikap dokter dalam memberikan surat keterangan cuti sakit. Hasil kuisioner dianalisa secara deskriptif. Hasil penelitian didapatkan 63% setuju setiap pasien mendapatkan surat keterangan cuti sakit, 60% tidak setuju hubungan kekerabatan mempengaruhi dokter dalam memberikan surat keterangan cuti sakit, 94% setuju pemberian lama cuti sakit merupakan hak/ kewenangan mutlak dokter, 71% tidak setuju jika dokter selalu memberikan surat keterangan cuti sakit kepada setiap pasien yang meminta, 74% dokter tidak pernah memberikan surat keterangan cuti sakit yang tidak sesuai dengan kondisi pasien, 60% dokter setuju dalam memberikan lama cuti sakit kadang-kadang mempertimbangkan permintaan pasien, 97% dokter tidak setuju menarik biaya tersendiri dalam pemberian surat keterangan cuti sakit. Disimpulkan bahwa persepsi dan sikap dokter di RS PKU Muhammadiyah Yogyakarta masih sesuai dengan kode etik kedokteran Indonesia.